2014
DOI: 10.1097/nor.0000000000000032
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Management of Tibia Stress Fractures

Abstract: The LPS&RT was an effective, uniform measure to standardize the plan of care for tibia stress fractures in one outpatient clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The epidemiology and clinical challenges associated with bone stress injuries in military training indicated the need for an updated algorithm to improve the timeliness and accuracy of diagnosis and treatment. Many existing algorithms for evaluation 23 , 24 , 32 and treatment 13 of stress fractures do not contain clinical prediction rules and/or rely primarily on bone scan. Of note, a recently published algorithm by Wright et al 32 is useful for the selection of proper imaging modalities but neither does it offer guidance on a threshold for beginning a diagnostic workup nor does it guide initial treatment steps.…”
Section: New Diagnostic Algorithmmentioning
confidence: 99%
“…The epidemiology and clinical challenges associated with bone stress injuries in military training indicated the need for an updated algorithm to improve the timeliness and accuracy of diagnosis and treatment. Many existing algorithms for evaluation 23 , 24 , 32 and treatment 13 of stress fractures do not contain clinical prediction rules and/or rely primarily on bone scan. Of note, a recently published algorithm by Wright et al 32 is useful for the selection of proper imaging modalities but neither does it offer guidance on a threshold for beginning a diagnostic workup nor does it guide initial treatment steps.…”
Section: New Diagnostic Algorithmmentioning
confidence: 99%
“…Most studies on TBSIs have focused on clinical outcomes (13,19,20) and do not examine the mechanical loading environment of bone when wearing a walking boot. Findings from studies focused on the biomechanics of walking boots found that they provide a reduction in forefoot pressure, but conflicting evidence suggest they moderately reduce or increase heel pressure (21)(22)(23)(24).…”
mentioning
confidence: 99%